Robotically assisted treadmill exercise training for improving peak fitness in chronic motor incomplete spinal cord injury: A randomized controlled trial. (January 2016) - Gorman, Peter H.; Scott, William; York, Henry; Theyagaraj, Melita; Price-Miller, Naomi; McQuaid, Jean; Eyvazzadeh, Megan; Ivey, Frederick M.; Macko, Richard F.
Abstract : Objective: To assess the effectiveness of robotically assisted body weight supported treadmill training (RABWSTT) for improving cardiovascular fitness in chronic motor incomplete spinal cord injury (CMISCI). Design: Pilot prospective randomized, controlled clinical trial. Setting: Outpatient rehabilitation specialty hospital. Participants: Eighteen individuals with CMISCI with American Spinal Injury Association (ASIA) level between C4 and L2 and at least one-year post injury. Interventions: CMISCI participants were randomized to RABWSTT or a home stretching program (HSP) three times per week for three months. Those in the home stretching group were crossed over to three months of RABWSTT following completion of the initial three month phase. Outcome measures: Peak oxygen consumption (peak VO2 ) was measured during both robotic treadmill walking and arm cycle ergometry: twice at baseline, once at six weeks (mid-training) and twice at three months (post-training). Peak VO2 values were normalized for body mass. Results: The RABWSTT group improved peak VO2 by 12.3% during robotic treadmill walking (20.2 ± 7.4 to 22.7 ± 7.5 ml/kg/min, P = 0.018), compared to a non-significant 3.9% within group change observed in HSP controls (P = 0.37). Neither group displayed a significant change in peak VO2 during arm cycle ergometry (RABWSTT, 8.5% (P = 0.25); HSP, 1.76% (P = 0.72)). A repeated measures analysis showed statistically significant differences between treatments for peak VO2 during both robotic treadmill walking (P = 0.002) and arm cycle ergometry (P = 0.001). Conclusion: RABWSTT is an effective intervention model for improving peak fitness levels assessed during robotic treadmill walking in persons with CMISCI.